Ayurvedic Management of Cervical Myelopathy (International Journal of Ayurveda and Pharma Research, 2024)
Cervical Myelopathy is a condition causing compression of the spinal cord at the cervical level of the spinal cord. It is mostly due to degenerative cervical spondylosis and is hence called Cervical Spondylotic Myelopathy.  The spinal cord may directly experience compressive and ischemic dysfunction as a result of age-related spondylotic alterations. A 63-year-old male with complaints of gradually progressive weakness in the arms and hands along with numbness, tingling sensation, neck stiffness and pain around the neck region for the last 10 years came to the OPD of our hospital. The management offered by contemporary medicine is not satisfactory. Cervical myelopathy and Greevastambha can be co-related in this case, based on signs and symptoms. This case report demonstrates how the clinical and radiological symptoms of cervical spondylotic myelopathy were alleviated by an Ayurvedic intervention. To confirm these results and incorporate Ayurveda into conventional medicine for spinal cord injuries, more investigation and controlled trials are necessary.